2015
DOI: 10.1097/ypg.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Lack of genetic association of the TGM2 gene with schizophrenia in a Chinese population

Abstract: The gene coding for transglutaminase 2 (TGM2) has been reported to be associated with schizophrenia in a White population. The present study was then designed to replicate this initial finding in a Chinese population. A total of 428 individuals with schizophrenia and 555 control participants were recruited for genetic analysis. Four single nucleotide polymorphisms present in the TGM2 gene were selected for genotyping, including rs2076380, rs7270785, rs4811528, and rs6023526, by PCR-based restriction fragment l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…61 TGM2 SNPs and a haplotype showed nominal association ( P ~0.0004) to schizophrenia in a family-based study of 131 British family trios, 62 though no association was found in a Chinese case–control study. 63 TGM2 has been reported (in a patent, US20070015152) to be upregulated in the brain (anterior cingulate cortex) of schizophrenia cases versus controls. Celiac disease has an epidemiological association with schizophrenia; gluten-free diets occasionally reduce psychotic symptoms; and circulating gliadin antibodies are elevated in schizophrenia cases versus controls (reviewed in Wang et al 63 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 TGM2 SNPs and a haplotype showed nominal association ( P ~0.0004) to schizophrenia in a family-based study of 131 British family trios, 62 though no association was found in a Chinese case–control study. 63 TGM2 has been reported (in a patent, US20070015152) to be upregulated in the brain (anterior cingulate cortex) of schizophrenia cases versus controls. Celiac disease has an epidemiological association with schizophrenia; gluten-free diets occasionally reduce psychotic symptoms; and circulating gliadin antibodies are elevated in schizophrenia cases versus controls (reviewed in Wang et al 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…63 TGM2 has been reported (in a patent, US20070015152) to be upregulated in the brain (anterior cingulate cortex) of schizophrenia cases versus controls. Celiac disease has an epidemiological association with schizophrenia; gluten-free diets occasionally reduce psychotic symptoms; and circulating gliadin antibodies are elevated in schizophrenia cases versus controls (reviewed in Wang et al 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…SOX10 [284], MOG (myelin oligodendrocyte glycoprotein) [285], TGM2 [286], LRRK2 [287], CD22 [288], GPR17 [120], TF (transferrin) [289], RELN (reelin) [290], DYSF (dysferlin) [291], HOXA5 [292], REN (renin) [293], CNTN1 [294], SLC1A1 [295], TLR2 [296], WT1 [297], MOBP (myelin associated oligodendrocyte basic protein) [298], MYRF (myelin regulatory factor) [299], IL7R [300], MBP (myelin basic protein) [151], SHH (sonic hedgehog signaling molecule) [301], NTSR1 [302], BMP2 [303], ERMN (ermin) [304], MMP3 [305], HLA-DRB5 [306], HLA-DMB [307], HLA-DRB1 [308], HLA-DRA [309], CASP1 [310], OAS1 [311], DCLK1 [312], EGFR (epidermal growth factor receptor) [313], COMT (catechol-O-methyltransferase) [314] and CIITA (class II major histocompatibility complex transactivator) [315] have a significant prognostic potential in multiple sclerosis. SOX10 [316], MOG (myelin oligodendrocyte glycoprotein) [317], CNGB1 [318], TGM2 [319], LRRK2 [320], CHRNA4 [321], RELN (reelin) [322], HTR2C [323], RIT2 [324], ACSL6 [325], C6 [326], REN (renin) [327], OLIG2 [328], TLR2 [329], SEMA3D [330], PCDH15 [331], FGF14 [332], TSPAN8 [333], ACAN (aggrecan) [334], SHH (sonic hedgehog signaling molecule) [335], P2RX7 [336], NTSR1 [337], RBP4 [338], TACR3 [339], ERBB3 [340], ERMN (ermin) [341], CDH13 [342], CSMD1 [343], NTF3 [344], FRMPD4 [345], GRIA4 [346], GRIA2 [347], SNCB (synuclein beta) [348], NR3C2 [349], MMP3 [350], GABRB2 [351], HLA-DRB1 ...…”
Section: Discussionmentioning
confidence: 99%
“…Immune system [51], axon guidance [52], metabolism [53], diseases of metabolism [54] and neuronal system [55] were lined with advancement of BD. Altered expression of SLC6A9 [56] and RHD (Rh blood group D antigen) [57], CHRFAM7A [58], ANXA3 [59], SLC1A5 [60], KCNH2 [61], HP (haptoglobin) [62], SELENBP1 [63], SNCA (synuclein alpha) [64], TGM2 [65], PINK1 [66], B2M [67], QPCT (glutaminyl-peptide cyclotransferase) [68], CBS (cystathionine beta-synthase) [69], NQO2 [70], GLRX5 [71], BASP1 [72], GAS7 [73], GPX1 [74], OLIG2 [75], RPTN (repetin) [76], IL33 [77], SOX10 [78], GRIK1 [79], ZFPM2 [80], SHANK3 [81], ERBB3 [82], ARC (activity regulated cytoskeleton associated protein) [83], GFAP (glial fibrillary acidic protein) [84], PLAT (plasminogen activator, tissue type) [85], GRIK5 [86], CACNB2 [87], NRXN2 [88], TERT (telomerase reverse transcriptase) [89], GNB3 [90], L1CAM [91], EGR3 [92], CAV1 [93], CACNA1B [94], MAGI1 [95], KIR2DL1 [96], PAH (phenylalanine hydroxylase) [97] and CYP3A5 [98] have been shown in schizophrenia. Recent studies showed that SLC6A9 [99], FKBP1B [100], S100A12 [101], SLC6A19 [102], TXN (thioredoxin) [103], TLR9 [104], HP (haptoglobin) [105], ARG1 [106], PINK1 [107], B2M [108], C5AR1 [109], MYADM (myeloid associated differentiation marker) [110], CBS (cystathionine beta-synthase) [111], GPX1 [112], SIAH2 [113], PRDX2 [114], RDH8 [115], CYP11B2 [116], RARRES2 [117], NOX1 [118], IL33 [119], OTC (ornithine transcarbamylase) [120], CYP1A1 […”
Section: Discussionmentioning
confidence: 99%